Herding behavior, disposition effect & investment decision: Testing the role of risk perception - Khairunnisa Khairunnisa; Heriyadi Heriyadi; Wendy Wendy; Ilzar Daud; Rizani Ramadhan (International Journal of Applied Finance and Business Studies, 2023)
This study explores how herding behavior, disposition effect, and risk perception affect the investment decisions of college students, with risk perception as a moderating variable. The survey involved selecting 210 respondents using a purposive sampling technique. This research examined the association between independent and dependent variables using AMOS and SPSS to test the hypotheses. The Structural Equation Model (SEM) test results show that risk perception is not a moderating factor in the relationship between herding behavior and investment decisions. How individuals perceive risk can impact how the disposition effect influences investment decisions. The study’s findings indicated that herding behavior, the disposition effect, and risk perception strongly impact investment decisions.